Sensitivity of broiler performance, organ weights and plasma constituents to amino acid supplementation and reused litter exposure using ideal protein-formulated rations - M.A. Hussein; F. Khattak; L. Vervelde; S. Athanasiadou; J.G.M. Houdijk (Animal, 2023)
Effects of amino acid supplementation to ideal protein (IP) formulated rations were investigated on growth performance, plasma metabolites and organ weights of broilers placed on 100% recycled (reused) litter. Day-old Ross308 male broilers were raised on either clean or reused litter and fed for three weeks on one of five isoenergetic diets, where an IP-based control diet (C) was compared with diets containing threonine (T) or arginine (A) at 25% above requirements, or with 1% supplemented glutamine (G), or with each amino acid added (TAG). Litter and diet treatments did not strongly interact on outcomes. Reused litter placement resulted in greater weight gain, smaller feed conversion ratio and heavier bursal weights (P < 0.05) compared to clean litter placement. Relative to C and T birds, TAG birds reduced weight gain and feed intake (P < 0.05). Plasma uric acid levels in G birds were greater than in C, T and A birds (P < 0.001). Collectively, since the outcomes of placement on reused litter increased performance and the control diet was IP formulated, the absence of increased growth performance in response to amino acid supplementation would be consistent with amino acids tested being excess to requirements.